Eine gerechte und aufkommensneutrale Grundsteuerreform? - Thomas Eigenthaler; Gisela Färber; Gerd Landsberg; Stefan Homburg; Ralph Henger; Thilo Schaefer (Wirtschaftsdienst, 2018)
Nach einer fast 20-jährigen Vorgeschichte hat sich das Bundesverfassungsgericht (BVerfG) mit der Bemessungsgrundlage der Grundsteuer beschäftigt. Dabei geht es um die veralteten Einheitswerte, aber auch um die Gesetzgebungskompetenz für das geltende Bewertungsgesetz. Die Autoren diskutieren über verschiedene Reformmodelle, das Volumen der Grundsteuer sowie deren Aufkommensneutralität, deren Folgen für die Verteilung und den Länderfi nanzausgleich. Welches Reformmodell sich durchsetzt, hängt auch davon ab, inwieweit es von den Bürgern akzeptiert wird. Bei einem komplizierten Verfahren ist zu befürchten, dass die Umstellung einen sehr langen Zeitraum in Anspruch nehmen wird, was der Akzeptanz schaden und weitere juristische Auseinandersetzungen provozieren könnte. – – After 20 years of political and legal disputes, the German Federal Constitutional Court will render a judgment on the constitutional compliance of the property tax in the course of 2018. The underlying question is whether the actual unit value has to be considered an outdated tax base and thus should be reformed. But there are different proposed reform options, some of which are funda men- tal, such as the land value tax. The property tax reform affects the distributive incidence of the local property and the federal tax revenue equalisation. In order to speed up the reform process, it may be crucial to simplify the regulation of the tax base. The reform has to avoid overburdening the citizens, but since it constitutes the crucial pillar for local self-government, it should not reduce local revenues. Since the property tax violates the ability-to-pay principle anyway, one author proposes a simpler design that preserves municipal an d state revenues and also inhibits overall tax increases.
Keywords: H23; H71; R38; 330